2020
DOI: 10.1109/trpms.2020.3002658
|View full text |Cite
|
Sign up to set email alerts
|

Gas Plasma Technology—An Asset to Healthcare During Viral Pandemics Such as the COVID-19 Crisis?

Abstract: The COVID-19 crisis profoundly disguised the vulnerability of human societies and healthcare systems in the situation of a pandemic. In many instances, it became evident that the quick and safe reduction of viral load and spread is the foremost principle in the successful management of such a pandemic. However, it became also clear that many of the established routines in healthcare are not always sufficient to cope with the increased demand for decontamination procedures of items, healthcare products, and eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 108 publications
0
29
0
Order By: Relevance
“…Cold atmospheric pressure plasmas (CAPs) have been increasingly used as a tool for air sterilization and decontamination. [ 20,21 ] CAPs generate many reactive oxygen and nitrogen species as O 3 , NO, NO 2 , N 2 O 5 , HNO 2 , HNO 3 , ONOO − , H 2 O 2 , normalOnormalH, and many other reactive species, that can react with the airborne particles and mediate various oxidative processes. [ 22–25 ] Due to the associated electric field, nonthermal plasmas (NTPs) can alter particle transport by inducing a negative charge on the particles, thus imparting charge‐driven filtration as well as trapping of these particles.…”
Section: Introductionmentioning
confidence: 99%
“…Cold atmospheric pressure plasmas (CAPs) have been increasingly used as a tool for air sterilization and decontamination. [ 20,21 ] CAPs generate many reactive oxygen and nitrogen species as O 3 , NO, NO 2 , N 2 O 5 , HNO 2 , HNO 3 , ONOO − , H 2 O 2 , normalOnormalH, and many other reactive species, that can react with the airborne particles and mediate various oxidative processes. [ 22–25 ] Due to the associated electric field, nonthermal plasmas (NTPs) can alter particle transport by inducing a negative charge on the particles, thus imparting charge‐driven filtration as well as trapping of these particles.…”
Section: Introductionmentioning
confidence: 99%
“…Cold plasma has demonstrated great potential for inactivation of SARS-CoV-2. 10 , 87 , 88 , 89 , 90 Since it does not generate waste or toxic chemicals, this method is seen as environmentally friendly. This technique also has potential with extensive applications in the disinfection of food surfaces, equipment, and food packages.…”
Section: Limitation Of Sars-cov-2 Spreadmentioning
confidence: 99%
“…These studies showed that cold plasma could be an effective method to avoid transmission and infections on various surfaces. 89 , 101 Also, Verma (2020) has reported that application parameters such as duration should be optimized for the elimination of viruses on the contaminated material. 94 In terms of food products, inactivation of the Tulane virus on spinach, 102 murine norovirus-1 and hepatitis A virus on fresh meats, 95 norovirus surrogates on blueberries 97 and some other food systems, 103 Tulane virus on romaine lettuce, 104 and Newcastle disease virus on poultry 105 was effectively applied by cold plasma treatment.…”
Section: Limitation Of Sars-cov-2 Spreadmentioning
confidence: 99%
“…Brought into focus by the current COVID-19 pandemic, it is no longer limited to medical, pharmaceutical, or food industry, but rather expanded to the decontamination of commonly used surfaces such as doorknobs and devices, such as masks, cell phones, and pens. Over the last two decades, cold atmospheric pressure plasmas (CAP) have seen rapid development in the areas of bacterial and viral inactivation and surface disinfection 1 8 . A recent review 8 summarizes the achievements of a broad range of CAP plasma sources, including dielectric barrier discharges (DBD), that effectively inactivate bacteria, viruses, fungi, and bacterial spores.…”
Section: Introductionmentioning
confidence: 99%